2014
DOI: 10.1007/s00606-014-1074-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny, karyotype evolution and taxonomy of Crocus series Verni (Iridaceae)

Abstract: The taxonomically complicated Crocus series Verni is characterized by high intra-and interspecific variability of karyotypes (2n = 8-23). With the aim to get more insights into complex karyotype evolution and to clarify the taxonomy of this group, we combined morphological (twelve characters), molecular (chloroplast DNA: trnL-trnF, ndhF; nuclear DNA: ITS, pCOSAt103) and karyological analyses. Samples of different populations of C. etruscus, C. ilvensis, C. kosaninii, C. tommasinianus, C. vernus sensu lato and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 44 publications
(58 reference statements)
4
41
0
1
Order By: Relevance
“…The genus Crocus L. consists currently of about 160 recognized species (Mathew, 1982;Petersen et al, 2008;Kerndorff and Pasche, 2011;Kerndorff et al, 2011Kerndorff et al, , 2013Peruzzi and Carta, 2011;Ranđelović et al, 2012;Harpke et al, 2014) occurring from western Europe and northwestern Africa to western China, with the center of species diversity on the Balkan Peninsula and in Turkey. Many crocuses are known as popular ornamentals, and saffron, the dried styles of C. sativus L., is one of the world's most expensive spices.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Crocus L. consists currently of about 160 recognized species (Mathew, 1982;Petersen et al, 2008;Kerndorff and Pasche, 2011;Kerndorff et al, 2011Kerndorff et al, , 2013Peruzzi and Carta, 2011;Ranđelović et al, 2012;Harpke et al, 2014) occurring from western Europe and northwestern Africa to western China, with the center of species diversity on the Balkan Peninsula and in Turkey. Many crocuses are known as popular ornamentals, and saffron, the dried styles of C. sativus L., is one of the world's most expensive spices.…”
Section: Introductionmentioning
confidence: 99%
“…For Cyananthus Wallich ex Bentham, 1836 (Campanulaceae) and for Crocus Linnaeus, 1753 ser. Verni Mathew, 1982 (Iridaceae), the data were derived by the recent papers by Chen et al (2014) and Harpke et al (2014), respectively. Most of these papers report also information on the phylogenetic relationships among groups (for Cyananthus available in Zhou et al 2013), as inferred from molecular systematic studies.…”
Section: Methodsmentioning
confidence: 99%
“…The occurrence of this species in Emilia-Romagna is a matter of debate since a long time. Currently considered as a narrow endemic to Toscana (Carta et al 2010, Harpke et al 2015, Peruzzi et al 2017, it was indeed doubtfully reported for Emilia-Romagna by Mathew (1982: "possibly also near Parma"), recorded by Alessandrini (1983), Alessandrini & Bonafede (1996), Alessandrini & Branchetti (1997), and Mazzoni et al (2001) for several localities. Later, it was excluded from the regional flora by Carta et al (2010) According to Bartolucci et al (2016b), this species was so far only historically recorded from Umbria.…”
Section: Lastrucci D Vicianimentioning
confidence: 99%